Pengembangan Sistem Informasi TEMASI (Teman Masa Isolasi) untuk Pemenuhan Kebutuhan Pasien COVID-19 berbasis Mobile - Ibrahimsyah Zairussalam; Fajar Pradana; Welly Purnomo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
The self-quarantine needs for COVID-19 patients are becoming limited as daily case of this virus keep increasing in Indonesia and the world. In a study explained that self-quarantined patient have to wait some time to get the needs such as oxygen tank, convalescent plasma, and foods. That situation causes people to find help by sending broadcast messages through social media. The information that spread over many social medias make it harder for people who want to give some donation to find that information, and since the content of social media is very diverse, sometime causes the information cannot be found by others. Therefore, this research is conducted to build an information system TEMASI (Teman Masa Isolasi) that can be an information center so people who needs some help can meet people who wants to give them help. This system will be built using waterfall method that is chosen because all the system requirements can be defined clearly at the beginning of the development phase. The system will be mobile based so it can be used anywhere and anytime. The system will be built using React Native framework to support multi-platform application. The system itself will be tested using both functional and usability test. The functional system validation test produces a result that the system has 100% success rate. At the usability test, the system has System Usability Scale (SUS) score of 73.25 for patient and 73.75 for the donor. Those scores make this system included in acceptable category so it can be used by users.